MANAGING DIVERSITY: THE GAP BETWEEN THEORIES AND PRACTICES IN THE HOSPITALITY INDUSTRY - Rahmawati, Putu Indah (JURNAL KEPARIWISATAAN, 2009)
Managing diversity becomes one of the most important/actors in ensuring company competitiveness. This paper explores the theories about diversity management and compares them with the practices in organizations a11d then examines late organizations' diversity programs I/trough their employees' perceptions. The findings illustrate that there is a gap between managing diversity theories and practices in organizations and some barriers in implementing diversity program, especially ill the hospitality industry. Therefore, it is suggested that human resources practices that make one conse11sus about the precise definition of workforce diversity as a guideline in developing diversity training programs. Organizations also need to change their approach from a reactive approach to a proactive approach toward workforce diversity. Communication told openness to dissimilarity can reduce the barriers in implementing diversity programs.